WEB OF SCIENCE BASED BIBLIOMETRIC ANALYSIS STUDY: TUBERCULOSIS MENINGITIS FROM 1970 TILL TO PRESENT - Alkan, Sevil; Celik, Mehmet; Gürbüz, Esra (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Tuberculous meningitis (TBM) is the most dangerous and incapacitating type of tuberculous and has a high mortality rate. Objective: We aimed to reveal the general perspective of tuberculous meningitis, with bibliometric analysis. Methods: This study included only articles as a document type, searched in the Web of Science database, indexed in ‘‘Science Citation Index Expanded’’ and ‘‘Emerging Sources Citation Index’’ from 1970 to the present. Results: A total of 2370 publications were reached and 1516 articles were included in the study. 87.401% of them were published in Science Citation Index Expanded and 12.599% in the Emerging Sources Citation Index. The articles were mostly published in English (92.084%) language. Most of the articles (6.266%) were published in 2021. 107 countries contributed to the tuberculous meningitis literature. India, the USA, and South Africa were the countries with the highest number of articles published. Most articles were published in “The International Journal of Tuberculosis and Lung Disease’’ journal. The countries that financially supported tuberculous meningitis studies the most were the USA and the United Kingdom (UK). Conclusion: TB continues to be an important public health problem globally, especially in low-middle-income countries. In this study, it was observed that there has been a significant increase in publications related to TBM in recent years. It was seen that the USA and UK were the countries that provided the most publications and financial support to the studies, although they were not, particularly the countries where TBM was watched most frequently.